Disagi dell’individuo ai tempi della pandemia - Michela Luzi (Culture e Studi del Sociale)
Covid-19 was an unforeseen event, which nullified the individual’s conviction of having everything under control, the illusion of living in a world protected from the intrusion of the imponderable and enclosed in the great caveau of progress. The epidemic storm has revealed the fragility of man’s cognitive, emotional and spiritual worlds. A virus as lethal as it is global, which has inoculated the poison of imponderability, feeding a state of tautological fear that puts into circulation a series of unknowns. The unknown of contagion, the thinning of social spaces, the imposition of isolation in physical space, all amplified by the time dilation and questioning of the extended present, which characterizes contemporary society. All this shows the amazing epiphany of an enemy as unusual as dangerous, which imposes social disintegration in order to contain the contagion, but which devastates fabric of society.